Assessing concurrent effects of climate change on hydropower supply, electricity demand, and greenhouse gas emissions in the Upper Yangtze River Basin of China. (1st December 2020) - Qin, Pengcheng; Xu, Hongmei; Liu, Min; Xiao, Chan; Forrest, Kate E.; Samuelsen, Scott; Tarroja, Brian
Highlights: Modeled climate change impacts on hydropower in Upper Yangtze River Basin in China. Assessed simultaneous climate change effects on electricity supply and demand. Translated climate supply–demand gap to greenhouse gas emissions implications. Climate change exacerbates supply–demand gap seasonally and inter-annually. Low-carbon resources are critical for reduce emissions from the supply–demand gap. Abstract: Hydropower importantly provides flexible low-carbon electricity, however, climate change will affect the hydropower system through altering hydrologic regimes while also affecting electricity demands for heating and cooling that hydropower resources serve. This study assesses the effect of climate change on hydropower and electricity demand in the Upper Yangtze River Basin (UYRB) in China on the regional net electric load and greenhouse gas (GHG) emissions. This is accomplished by using climate projections from five global climate models (GCMs) to simultaneously force (1) a physically-based hydrological model and a statistically-based hydropower model to estimate the future generating capacity of 21 large hydropower plants in the UYRB and (2) an empirical electricity demand model accounting for socioeconomic and climatic factors. Under climate change, the projected hydropower generation in the UYRB tends to increase in the 21st century but is far less than the increase in electricity demand, increasing the gap between demand and supply. Future increases in overall electricity demand are driven by GDP growth, but climate change will alter the distribution of the seasonal electricity demand. Climate warming decreases electricity demand for heating in winter and increases electricity demand for cooling in summer, but ultimately increases demand. Meanwhile, there is an increasing mismatch between electricity demand and hydropower supply associated with inter- and intra-annual variations, owing to the temporal climate change and increase in compound climate extremes (droughts and heatwaves). Finally, meeting the gap between supply and demand due to climate change is estimated to contribute 79.0–184.6 and 50.6–316.2 MMT CO2e /yr of additional GHG emissions by the mid and end of 21st century, respectively.